Reduce (5²×2³×3)³×3² ÷ (2⁴×5³): Complex Exponential Expression

Question

Reduce the following equation:

(52×23×3)3×3224×53= \frac{\left(5^2\times2^3\times3\right)^3\times3^2}{2^4\times5^3}=

Video Solution

Solution Steps

00:00 Simply
00:05 We'll break down the parentheses into multiplications, being careful with brackets
00:35 According to the laws of exponents, any base (A) raised to power (M) raised to power (N)
00:40 equals the same base (A) raised to the product of the exponents (M*N)
00:45 We'll use this formula in our exercise, for each power of a power
02:00 We'll break down the multiplications and extract the different bases from the denominator
02:05 According to the laws of exponents, when multiplying powers with the same base (A)
02:09 we get the same base (A) raised to the sum of the exponents (M+N)
02:17 We'll use this formula in our exercise
03:12 We'll break down the fraction into 2 fractions with equal bases
03:22 According to the laws of exponents, when dividing powers with equal bases (A)
03:27 equals the same base (A) raised to the difference of the exponents (M-N)
03:32 We'll use this formula in our exercise, and subtract between the powers
03:47 And this is the solution to the question

Step-by-Step Solution

Let's reduce the given expression step-by-step using the laws of exponents.

The expression to simplify is:

(52×23×3)3×3224×53\frac{\left(5^2\times2^3\times3\right)^3\times3^2}{2^4\times5^3}

First, simplify the expression inside the bracket:

  • Apply the power of a power rule (am)n=am×n(a^m)^n = a^{m \times n} to each term:

    • (52)3=52×3=56(5^2)^3 = 5^{2 \times 3} = 5^6

    • (23)3=23×3=29(2^3)^3 = 2^{3 \times 3} = 2^9

    • (31)3=31×3=33(3^1)^3 = 3^{1 \times 3} = 3^3

  • Substitute back into the expression:

  • 56×29×33×3224×53\frac{5^6 \times 2^9 \times 3^3 \times 3^2}{2^4 \times 5^3}

Next, combine the powers in the numerator:

  • Use the product of powers rule am×an=am+na^m \times a^n = a^{m+n}:

    • Combine the 3s: 33×32=33+2=353^3 \times 3^2 = 3^{3+2} = 3^5

  • The refined numerator is 56×29×355^6 \times 2^9 \times 3^5.

Now, simplify the fraction using division of powers:

  • For 5's: 5653=563=53\frac{5^6}{5^3} = 5^{6-3} = 5^3

  • For 2's: 2924=294=25\frac{2^9}{2^4} = 2^{9-4} = 2^5

  • 3's remain 353^5, as they only appear in the numerator.

Therefore, the final expression is:

53×25×35\boxed{5^3 \times 2^5 \times 3^5}

Answer

53×25×35 5^3\times2^5\times3^5